The meaning of tri-junction point in laparoscopic gastric cancer surgery - Jian-Ping Gong (临床与病理杂志, 2026)
Objective: It is admitted that, within gastric cancer surgery, the right layers as well as appropriate spaces demobilized between the target carcinoma mass and peripheral parts are worthy properly researching. This article is trying to delineate the entrances to the right layers in alimentary tract cancer surgery, especially in laparoscopic gastric cancer, with a brand new conception called ‘Trijunction Point’, abbreviated as TJ point. Methods: Based on experienced laparoscopic surgeons indications and microscopy histological slices observation on dissected peripheral adipose tissues in laparoscopic gastric cancer surgery. Results: The TJ points have been found located in different parts of abdominal mesenteries. Conclusion: The four TJ points in gastric peripheral adipose can be useful to guide a bloodless laparoscopic surgery with a promising start.